2011
DOI: 10.1002/sia.3528
|View full text |Cite
|
Sign up to set email alerts
|

Molecular depth profiling with reactive ions, or why chemistry matters in sputtering

Abstract: We have shown in recent papers that low-energy Cs + ions can be used successfully for molecular depth profiling of polymers. This paper reviews a few key experiments that provide a better understanding of the mechanisms involved in reactive ion depth profiling. It is shown that damaged polymer (polystyrene and polycarbonate) layers, initially bombarded with high-energy gallium irradiation, can be efficiently removed by low-energy Cs + sputtering so that the polymer molecular signal is restored. The role played… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Intensity oscillations are also noticed at the organic/ metal interface. This behavior is common with low energy Cs + depth profiling as was shown in previous works [18,24]. The initial drop is caused by rapid fragmentation of the Tyr molecules induced by the Cs + ions, leading to the formation of free radicals.…”
Section: Organics On Metalssupporting
confidence: 73%
See 1 more Smart Citation
“…Intensity oscillations are also noticed at the organic/ metal interface. This behavior is common with low energy Cs + depth profiling as was shown in previous works [18,24]. The initial drop is caused by rapid fragmentation of the Tyr molecules induced by the Cs + ions, leading to the formation of free radicals.…”
Section: Organics On Metalssupporting
confidence: 73%
“…Cs high reactivity ensures a negative ion signal enhancement, along with free radicals scavenging [18]. This source already proved its efficiency on both inorganics [19][20][21][22] and organics [23][24][25].…”
Section: Introductionmentioning
confidence: 87%
“…The pre‐sputtering of the surface before analysis should remove the preparation medium and any surface contamination as well as removing some of the cell wall to gain access to intracellular material. Several ion sources have been shown to be suitable for the sputtering of organic materials with low damage accumulation, of these, argon clusters, C 60 and low‐energy Cs are among the most popular. In this study we chose to use low‐energy (250 eV) Cs sputtering as this sputter source is present in the majority of TOF‐SIMS instruments (unlike argon clusters and C 60 ).…”
Section: Methodsmentioning
confidence: 99%
“…A decade ago, cluster ions started to be used in a quite general fashion for SIMS analysis, and it was found that with clusters such as SF 5 + and C 60 + , many polymers could be depth‐profiled with retention of the molecular information, i.e., with minimal damage to the new surface uncovered by the sputtering event, paving the way to molecular depth‐profiling and 3D molecular imaging . In parallel, the erosion of the sample with low energy (100–500 eV) Cs + ions was proposed as an alternative for molecular depth‐profiling, capitalizing on the combination of the limited damage induced by the low energy ions together with the ionization probability increase provided by the presence of Cs implanted in the subsurface …”
Section: Sims: From Surface Analysis To Molecular Depth Profiling Andmentioning
confidence: 99%